COVID-19 symptoms and SARS-CoV-2 antibody positivity in a large survey of first responders and healthcare personnel, May-July 2020 - Akinbami, Lara J (Clin Infect Dis, 2021)
A SARS-CoV-2 serosurvey among first responder/healthcare personnel showed that loss of taste/smell was most predictive of seropositivity; percent seropositivity increased with number of COVID-19 symptoms. However, 22.9% with nine symptoms were seronegative, and 8.3% with no symptoms were seropositive. These findings demonstrate limitations of symptom-based surveillance and importance of testing.